Study of Renal Volume and Functional Changes in Unilateral Nephrectomy –Our Institutional Experience - Mahesh Borikar; Bala Murali Krishna Patibandla; Ch Vishwajith Reddy; Mallipeddi Partha Sri; Arvind Kumar Prabhat; Subbarao Chodisetti (International Journal of Health and Clinical Research, 2022)
Introduction: A nephrectomy is the surgical removal of a kidney, performed to treat a number of kidney diseases including kidney cancer. It is also done to remove a normal healthy kidney from a living or deceased donor, which is part of a kidney transplant procedure. Both size and functions, primarily glomerular filtration rate (GFR) and renal plasma flow (RPF), increase almost immediately following unilateral nephrectomy. Aim: To determine short term differences in contralateral renal function and volume in unilateral nephrectomy patients in our institution. Material and Methods: This is a prospective study, Observational and cross-sectional study of all patients who undergo nephrectomy for renal transplantation, malignancy and other renal diseases at Tertiary Care Teaching Hospital over a period 1 year. A total of 62 patients who undergo open or laparoscopic nephrectomy have been assessed during the study period. The detailed history of all patients has been recorded. Results: We evaluated a total of 62 patients who underwent nephrectomy for various reasons. In all types of nephrectomy, groups post nephrectomy improvement in GFR and kidney volume to a varying extent was noted. When compared to the other two groups donor nephrectomy group is showing higher postoperative GFR with kidney volume and more improvement as compared to their preoperative values. The mean difference is shown in the table for each nephrectomy group, and for each group, it has a p-value <0.05. Similarly, for RPV improvement donor nephrectomy group shows the highest mean difference, and the diseased nephrectomy group shows the lowest mean difference. The difference in means of all nephrectomy is significant and has p-value <0.05. Conclusion: The DTPA-GFR and RPV of contralateral kidney increased steadily after surgery in all nephrectomised groups. Difference in functional and volumetric outcome after unilateral nephrectomy, can be arranged in decreasing order as donor nephrectomy group, radical nephrectomy group and then diseased nephrectomy group. The change in RPV and GFR of contralateral kidney after nephrectomy will help to predict compensatory response in healthy as well as co-morbid patients.